Applying the UTAUT Model to Understand Factors Affecting Micro-Lecture Usage by Mathematics Teachers in China - Tommy Tanu Wijaya; Yiming Cao; Robert Weinhandl; Eri Yusron; Zsolt Lavicza (Mathematics, 2022)
In the last decade, micro-lectures have been widely used to teach mathematics, but only a few studies have examined the factors affecting teachers’ intentions of using micro-lectures. As teachers are key to integrating modern technologies such as micro-lectures into students’ learning processes, knowledge about teachers’ intentions in this regard could be of particular importance. This study aimed to analyze the behavioral intention (BI) of mathematics teachers in using micro-lectures in mathematics in China, and identify the most influential factors involved, for the very first time. The Unified Theory of Acceptance and Use of Technology (UTAUT) model was used as a design model to investigate teachers’ BIs concerning the use of micro-lectures, and we used an online questionnaire to collect quantitative data. The participants in our research were 174 mathematics teachers from China, 166 of whom provided us with evaluable questionnaire data. Furthermore, partial least squares (PLS) regression was used, and hypothesis testing was performed with the Smart-PLS software. From the results, BI was positively affected by Performance Expectancy (PE), Effort Expectancy (EE), and Social Influence (SI). BI and facility conditions also had positive effects on user behavior; in contrast to other studies, SI had the most significant positive effect on BIs in our study. Our findings could provide insights into both future strategies for successful technology integration in mathematics classes and into mathematics teachers’ intentions towards integrating technologies into mathematics teaching.